Efektivitas dan Efisiensi Penggunaan Dana Desa terhadap Pembangunan Ekonomi dan Kesejahteraan Masyarakat di Desa Sukaraja, Lampung Selatan - Sonia Simanullang; Ambya .; Heru Wahyudi; Prayudha Ananta (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
Village Fund management is a strategic government instrument for promoting village development and improving community welfare. However, the effectiveness and efficiency of its utilization remain challenges, particularly related to transparency, accountability, and human resource capacity at the village level. South Lampung Regency, as a recipient of Village Funds, faces challenges in optimizing the use of funds for economic development and community empowerment. This study aims to evaluate the effectiveness and efficiency of Village Fund management in supporting economic development and improving community welfare in South Lampung Regency. This study employed a mixed methods approach with a descriptive approach. The study population was village officials and the community in South Lampung Regency, with a purposive sampling method. Data collection techniques included interviews, observations, and documentation studies. Data sources consisted of primary and secondary data, analyzed using qualitative and quantitative descriptive analysis techniques. The results indicate that Village Fund management has had a positive impact on infrastructure development, increased economic access, and community empowerment. However, strengthening oversight mechanisms, increasing community participation, and developing the capacity of village officials are crucial steps to improve the effectiveness and efficiency of Village Fund management. This optimization is expected to promote sustainable village development and significantly improve community welfare.